Investigating Remote and Live Lessons through Collaborative Tools during Covid-19 Quarantine: Experience Report (Research, Society and Development, 2020)
Towards the current scenario in which human beings live, where people are lock downed and in quarantine period in Brazil and in the world, it arises an important question: how teaching-learning has been organized, at the most different levels of education. Distance learning (DL) offers a variety of tools and techniques, in which web conferencing/video conferencing stands out at the moment.  The web conference and its resources have become available for performing remote and live classes, in a model where docent and pupils meet on the same day and schedule for promoting teaching and learning. This paper aims to investigate the resource of remote and live classes, through collaborative tools, such as web conferencing, towards the scenario of lockdown and Covid-19 that is presented. As methodology, it was applied one questionnaire to forty-one teachers, to identify and analyze their practices. Besides, it was made an author's experience report. It was realized the docent’s effort to review his pedagogical strategies, as preliminary results, through the use of ICTs, remote classes and distance learning.